Effects of guanidinoacetic acid supplementation on growth performance, hypothalamus-pituitary-adrenal axis, and immunity of broilers challenged with chronic heat stress - Xin Li; Jiawei Bian; Tong Xing; Liang Zhao; Jiaolong Li; Lin Zhang; Feng Gao (Poultry Science, 2023)
ABSTRACT: Heat stress can cause systemic immune dysregulation and threaten the health of broilers. Guanidinoacetic acid (GAA) has been shown to be effective against heat stress, but whether it is beneficial for immunity is unclear.Therefore, the effects of dietary GAA supplementation on the immunity of chronic heat-stressed broilers were evaluated. A total of 192 Arbor Acres male broilers (28-day old) were randomly allocated to 4 treatments: the normal control group (NC, 22°C, ad libitum feeding), the heat stress group (HS, 32°C, ad libitum feeding), the pair-fed group (PF, kept at 22°C and received food equivalent to that consumed by the HS group on the previous day), and the GAA group (HG, 32°C, ad libitum feeding; basal diet supplemented with 0.6 g/kg GAA). Samples were collected on d 7 and 14 after treatment. Results showed that broilers exposed to heat stress exhibited a decrease (P < 0.05) in ADG, ADFI, thymus and bursa of Fabricius indexes, and an increase (P < 0.05) in feed conversion ratio and panting frequency, compared to the NC group. Levels of corticotropin-releasing factor, corticosterone (CORT), heat shock protein 70 (HSP70), IL-6, and TNF-α were elevated (P < 0.05) while lysozyme and IgG concentration was decreased (P < 0.05) in the HS group compared with the NC group after 7 d of heat exposure. The concentrations of IgG and IL-2 were decreased (P < 0.05) and CORT was increased (P < 0.05) in the HS group compared with the NC group after 14 d of heat exposure. Noticeably, GAA supplementation decreased the levels of CORT (P < 0.05) and increased the IL-2, IgG, and IgM concentrations (P < 0.05) compared with the HS group. In conclusion, chronic heat stress increased CORT release, damaged immune organs, and impaired the immunity of broilers. Dietary supplementation of 0.6 g/kg GAA can reduce the CORT level and improve the immune function of broilers under heat stress conditions.